Health Assessment of Internal Hygiene Control in Sauce Production - Tsvetelina Vitkova (Journal of Biomedical & Clinical Research, 2021)
Nowadays, usage of sauces as part of a meal has seen a significant increase. In their diversity as raw materials and technology of production, sauces are a potential source of health problems. During their production, primary and secondary contamination with microorganisms and other physical or chemical contaminants is possible. Ineffective internal control is a prerequisite for the emergence of health problems among consumers. The subject of the study is а sauce manufacturer. An algorithm was designed to perform the audit and for the purposes of the. The prerequisite measures were placed in separate Good Hygiene Practices (GHP) and Good Manufacturing Practices (GMP) programs and in the technological documentation for all the sauces produced, with plans, procedures, orders, instructions, lists, registers and other documents, all closely related to the specifics of production. The technological documentation was found to be in agreement with the Food Safety Management System – the HACCP-plan. The technological documentation, which is part of the prerequisite measures, corresponded to its purpose and, with slight adjustments, is a good basis for the effective functioning of the Food Safety Management System. The conclusions contain specific recommendations for revision of the Internal Control System, including correction of elements of health and hygiene importance.